2017
DOI: 10.3390/jcdd4040020
|View full text |Cite|
|
Sign up to set email alerts
|

Growth and Morphogenesis during Early Heart Development in Amniotes

Abstract: In this review, we will focus on the growth and morphogenesis of the developing heart, an aspect of cardiovascular development to which Antoon Moorman and colleagues have extensively contributed. Over the last decades, genetic studies and characterization of regionally regulated gene programs have provided abundant novel insights into heart development essential to understand the basis of congenital heart disease. Heart morphogenesis, however, is inherently a complex and dynamic three-dimensional process and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 100 publications
3
12
0
Order By: Relevance
“…However, bilateral heart tubes and chambers can form in the absence of either endocardium (Ferdous et al, 2009) or foregut endoderm constriction (DeHaan and DeHaan, 1959;Li et al, 2004), but the mechanism is still unknown. This indicates the inherent capability of cardiac mesoderm to intrinsically form cavities and chambers in vivo (Ivanovitch et al, 2017), which is in agreement with the self-organization we observed in cardioids and chick embryo explants in vitro. Lateral plate mesoderm, a subtype closely related to cardiac mesoderm, has a similar potential to form a cavity -the pericardial body cavity (Schlueter and Mikawa, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, bilateral heart tubes and chambers can form in the absence of either endocardium (Ferdous et al, 2009) or foregut endoderm constriction (DeHaan and DeHaan, 1959;Li et al, 2004), but the mechanism is still unknown. This indicates the inherent capability of cardiac mesoderm to intrinsically form cavities and chambers in vivo (Ivanovitch et al, 2017), which is in agreement with the self-organization we observed in cardioids and chick embryo explants in vitro. Lateral plate mesoderm, a subtype closely related to cardiac mesoderm, has a similar potential to form a cavity -the pericardial body cavity (Schlueter and Mikawa, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…We found that WNT and VEGF control CM and EC self-organization in cardioids. In vivo, cardiac ECs first form endocardial tubes, later become separated from the outer CM tube by an ECM-filled (cardiac jelly) interspace, and finally form the inner lining of the heart chambers (Abu- Issa and Kirby, 2007;Ivanovitch et al, 2017). How signaling coordinates these patterns and morphogenetic processes with specification was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…EC6 uniquely expressed genes involved in fatty acid (FA) binding and transport including CD36 , FABP4 , and FABP5 , thereby providing the basis for the FA-biased energy metabolism that contributes up to 70% of cardiac ATP ( Supplementary material online , Figure S3 ). Unexpectedly, fast skeletal muscle troponin TNNT3 is specifically expressed in EC6 in the foetal heart, which was further confirmed by immunohistochemistry ( Figures 2 D–F and 3 A ). Furthermore, blood vessels formed by EC6 are characterized also by the presence of perivascular cells surrounding them.…”
Section: Resultssupporting
confidence: 56%
“… 2 The cardiac progenitors arise from mesoderm and segregate into two populations that form first (FHF) and second (SHF) heart fields. 3 The FHF gives rise to the early cardiac tube that contributes to the left ventricle and parts of the atria whereas the SHF is placed within and at the entry of the developing tube and contributes to the outflow tract, right ventricle, and atria. 1 Genetic cell-fate-mapping studies in animal model systems have greatly enhanced the understanding of lineage contribution to diverse cell groups that constitute the heart.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the central role the cardiovascular system plays in the embryonic, foetal and postnatal life, the genetic and biomechanical factors regulating normal cardiovascular development and the mechanisms underlying its pathologies are the focus of biomedical research [1,2,3,4,5,6,7]. For such research, a large number of tools for labelling active genes and gene products and for modifying or physically challenging their interplay during critical steps of development and growth were created and successfully established.…”
Section: Introductionmentioning
confidence: 99%